Vulnerable habitat: architectural requirements in housing in risk areas of Jocotepec - Zambrano Prado, Perla; Chávez-Camarena, Tanya (Estoa. Journal of the Faculty of Architecture and Urbanism, 2025)
This study analyzes the spatial needs of families living in homes affected by ground subsidence in Jocotepec. The research involved residents from 17 households, using a mixed-methods approach that combined surveys and participatory dynamics as data collection tools. The results show that children represent 16% of the population and people with disabilities 3%. The most valued housing features include green areas (59%), spacious rooms (35%), good lighting (29%), and natural ventilation (24%). Other important aspects mentioned are accessibility, comfort, bedrooms with bathrooms, functional layout, and spaces for pets (6%). Additionally, the most requested extra spaces are gardens and bathrooms, both mentioned by 59% of the participants. Finally, the majority of residents expressed a preference for detached single-family housing typology.